Moonraker - Fleming, Ian, 1908-1964 (Fleming, Ian, 1908-1964. James Bond 007., 2012)
British secret agent James Bond investigates war hero Hugo Drax, the man behind Britain's top-secret Moonraker missile program, revealing a sinister past and a secret plan for the Moonraker.